Regulatory arbitrage and transnational surveillance: Australia's extraterritorial assistance to access encrypted communications - Monique Mann; Angela Daly; Adam Molnar (Internet Policy Review, 2020)
This article examines developments regarding encryption law and policy within 'Five Eyes' (FVEY) countries by focussing on the recently enacted Telecommunications and Other Legislation Amendment (Assistance and Access) Act 2018 (Cth) in Australia. The legislation is significant both domestically and internationally because of its extraterritorial reach, allowing the development of new ways for Australian law enforcement and security agencies to access encrypted telecommunications via transnational designated communications providers, and allowing for Australian authorities to assist foreign counterparts in both enforcing and potentially circumventing their domestic laws. We argue that Australia is the 'weak link' in the FVEY alliance as - unlike other FVEY members - has no comprehensive enforceable human rights protections. Given this, there is a possibility for regulatory arbitrage in exploiting these new surveillance powers to undermine encryption via Australia.
Keywords: 300; Encryption; Five eyes; Surveillance; Extraterritoriality